2016
DOI: 10.2527/jas.2015-9537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vaccination against foot-and-mouth disease virus on reproductive performance of Bos indicus beef cows

Abstract: This study compared reproductive performance of cows vaccinated against the foot-and-mouth disease (FMD) virus before timed AI or during early pregnancy (Exp. 1), as well as rectal temperature (RT) and plasma concentrations of the acute-phase protein haptoglobin in cattle vaccinated or not against the FMD virus (Exp. 2). Cattle utilized in Exp. 1 and 2 originated from herds with no historical occurrences of FMD and that received vaccination against the FMD virus biannually. In Exp. 1, 604 lactating, multiparou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…Therefore, the inflammation caused by intramuscular needle-syringe compared to IDAL vaccination resulted in higher levels of CRP and Hp 28 h after vaccination. Needle-free injections have been reported to reduce muscular damage and carcass defects [ 24 , 25 ]. Lower levels of APPs in the IDAL piglets 28 h after vaccination may indicate a reduced inflammation and muscular trauma due to the injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the inflammation caused by intramuscular needle-syringe compared to IDAL vaccination resulted in higher levels of CRP and Hp 28 h after vaccination. Needle-free injections have been reported to reduce muscular damage and carcass defects [ 24 , 25 ]. Lower levels of APPs in the IDAL piglets 28 h after vaccination may indicate a reduced inflammation and muscular trauma due to the injection.…”
Section: Discussionmentioning
confidence: 99%
“…Besides representing a substantial economic loss, the presence of tissue damage at the site of injection in pig carcasses is an indicator that pain occurred. Contrary to Houser et al [ 21 ] who did not report a significant difference in carcass lesions between vaccination methods, carcass defects (such as granuloma, abscess, and fibrosis) resulting from intramuscular injections of vaccines have been reported in some studies [ 24 , 25 ]. Needle-free injections might be expected to prevent possible tissue damage and bacterial contamination caused by needles.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, Stenfeldt et al (2011) reported a substantial induction of SAA, haptoglobin, and type 1 interferon in serum samples upon infection, which can be used as a marker of acute FMD virus infection in cattle. Furthermore, plasma haptoglobin was found to be maintained at higher levels in cattle vaccinated against FMD compared with the non-vaccinated control group at 7 dpv (Ferreira et al, 2016). Arthington et al (2013) noted that in both non-vaccinated steers or heifers and those vaccinated against Mannheimia haemolytica, APP (i.e., fibrinogen or haptoglobin) were elevated and plateaued at 3 dpi.…”
Section: Discussionmentioning
confidence: 97%
“…However, the vaccine administered by a needle syringe results in adverse effects such as pain, stress, broken needle residue in the carcass, tissue damage, and incidence of lesions at the injection sites such as neck and ham (Chase et al, 2008). A previous study found lesions such as granuloma, abscess, and fibrosis at the vaccination site in animal carcasses (Ferreira et al, 2016; Yeruham et al, 2001). In addition, Ko et al (2018) reported that the incidence of lesions in pork butt severely increased after FMD vaccination.…”
Section: Introductionmentioning
confidence: 89%